Behavioral and psychological symptoms of dementia in the long-term care setting: assessment of aged adults and intervention for caregivers - Duarte, Evelise Saia Rodolpho [UNESP]; Jacinto, Alessandro Ferrari [UNESP] (FapUNIFESP (SciELO), 2023)
Due to the progressive need for care, older adults with dementia are at risk of becoming institutionalized. Caregivers of these patients are tasked with the challenge of controlling behavioral and psychological symptoms without sufficient knowledge and are therefore at greater risk of developing physical and mental health problems. In this context, psychoeducational interventions can help greatly toward improving caregiver well-being. Objective: to investigate the prevalence of behavioral and psychological symptoms of dementia (BPSD) in aged residents of long-term care facilities (LTCFs), to determine the prevalence of burden and common mental disorders in caregivers, and to assess the effects of a psychoeducational intervention. Methods: an intervention study was performed at LTCFs for aged people. The following instruments were used: Self-Reporting Questionnaire and Zarit Burden Interview for caregivers; and the MMSE, Katz Index, Clinical Dementia Rating scale and Neuropsychiatry Inventory-Questionnaire for older adults. Results: Of the 72 aged residents assessed, 52 (72.2%) were female and mean age was 82.3 (±8.14) years. The most prevalent neuropsychiatric symptoms were euphoria and elation (74%), followed by agitation and aggression (74%). Of the 54 caregivers, 49 (90.7%) were women and mean age was 33.9 (±10.8) years. Overall, 33.3% screened positive for common mental disorder and 36.1% for burden/overload. A statistically significant association was found between burden and working in philanthropic institutions (p=0.003) and also between burden and presence of common mental disorder or otherwise (p=0.001). After the psychoeducational intervention, 42.8% reported reduced burden. Conclusion: The residents presented neuropsychiatric symptoms. Caregivers showed burden and common mental disorders, especially in philanthropic institutions. It was observed a reduction in burden of caregivers with psychoeducational intervention, showing the importance of this strategy.
Sintomas comportamentais e psicológicos na demência no contexto da longa permanência: avaliação de idosos e intervenção para cuidadores
Keywords: Aged; Caregivers; Dementia; Homes for the Aged